A Meta-Analysis of the Efficacy of Virtual Reality and In Vivo Exposure Therapy as Psychological Interventions for Public Speaking Anxiety. Issue 4 (July 2022) - Reeves, Rachel; Curran, David; Gleeson, Amanda; Hanna, Donncha
Public speaking anxiety (PSA) is a prevalent condition with disabling occupational, educational, and social consequences. Exposure therapy is a commonly utilized approach for treating PSA. Traditionally, this intervention has been delivered as in vivo exposure therapy (IVET). Limitations inherent to in vivo as a mode of delivery have been identified and studies have increasingly explored the use of Virtual Reality Exposure Therapy (VRET) as an alternative. Understanding the efficacy of both VRET and IVET as psychological interventions for PSA is important. A systematic search identified 11 studies with 508 participants. Meta-analysis yielded a large significant effect wherein VRET resulted in significant reductions in PSA versus control of −1.39 ( Z  = 3.96, p  < .001) and a similar large significant effect wherein IVET resulted in significant reductions in PSA versus control of −1.41 ( Z  = 7.51, p  < .001). Although IVET was marginally superior to VRET, both interventions proved efficacious. Given the advantages of utilizing VRET over IVET future research and clinical practice could explore VRET as a treatment option for PSA.